Ursolic Acid Decreases the Proliferation of MCF-7 Cell-Derived Breast Cancer Stem-Like Cells by Modulating the ERK and PI3K/AKT Signaling Pathways - Kim, Gi Dae (Preventive nutrition and food science, 2021)
Cancer stem cells are strong drivers of metastasis and cancer relapse, which makes them important therapeutic targets. Ursolic acid (UA), a pentacyclic triterpenoid, has anticancer effects in various types of cancer; however, little is known about its effect on the growth of MCF-7 cell-derived breast cancer stem (BCS)-like cells in estrogen receptor positive breast cancer. In this study, the anticancer activity of UA in MCF-7 cell-derived BCS-like cells and its mechanism of action were evaluated. Furthermore, its inhibitory effects on the proliferation of MCF-7 cell-derived BCS-like cells were compared with that on MCF-7 cells. In MCF-7 cells, UA increased p53 and p21 expression but decreased cyclin D, cyclin E, CDK4, and CDK2 expression to induce cell cycle arrest in the G0/G1 phase. Moreover, UA significantly suppressed migration, invasion, and colony formation in MCF-7 cells, and suppressed mammosphere formation in a concentration- dependent manner. In MCF-7 cell-derived BCS-like cells, UA significantly decreased migration, suppressed p-PI3K, p-AKT, and p-ERK expression, and enhanced p-FoxO1/FoxO3a expression. Accordingly, in MCF-7 cell-derived BCS-like cells, UA suppressed proliferation in part by downregulating ERK and PI3K/AKT signaling pathways. These findings provide the first evidence for the selective effects of UA in BCSs.